EVALUASI PENATAAN RUANG LUAR RUMAH SAKIT UMUM DAERAH (RSUD) SOLOK SELATAN - Syukria Dista Alfigusti; Effan Fahrizal; Fidyati (Rumoh Journal of Architecture, 2022)
Regional Public Hospital of Solok Selatan is the only hospital in South Solok which has quite complete facilities, making thishospital visited by various levels of society. This hospital has a large building with minimal open areas, also the mass of thebuilding and the irregular layout plan cause poor circulation and the formation of dead (negative) outer space. Elements ofoutdoor space design consist of space divider/mass composition, green layout and circulation. The purpose of this studywas to define whether the results of the outer space arrangement evaluation of Regional Public Hospital Solok Selatan hadmet the standard. The type of research conducted in the study area was descriptive research with a qualitative approach.The qualitative approach was made through data collection activities, data compilation, data analysis, and study literature asa research reference. The results showed that the arrangement of the outer space in the outdoor layout, the circulation ofthe walkway, and the emergency route did not meet the standards, while in contrast, the circulation of the entrances andexits had met the standards.